Cystatin C: A Marker for Inflammation and Renal Function Among HIV-infected Children and Adolescents. Issue 2 (February 2016) - Deyà-Martínez, Àngela; Fortuny, Clàudia; Soler-Palacín, Pere; Neth, Olaf; Sánchez, Emília; Martín-Nalda, Andrea; Falcón-Neyra, Lola; Vila, Anna; Valls, Anna; Noguera-Julian, Antoni
Abstract : Background: Renal disease is a leading cause of morbidity in HIV-infected adults in the highly active antiretroviral therapy (HAART) era. Cystatin C has been proposed as a more sensitive marker of renal function, but it may be affected by ongoing inflammation. We aimed to study the cystatin C levels in a cohort of HIV-infected pediatric patients at 3 Spanish centers. Methods: This is a multicenter cross-sectional observational study. Renal function was assessed by means of first morning urine protein/creatinine and albumin/creatinine ratios and creatinine-estimated glomerular filtration rates (GFRs), together with the following inflammation markers: cystatin C, reactive C protein, β-2-microglobulin and 25(OH)-vitamin D levels. A control group of healthy children and adolescents was used. Results: Eighty-three patients (51 females, median age: 13.3 years; 32 males, median age: 13.6 years) and 44 controls (24 females, median age: 12.2 years; 20 males, median age: 10.9 years) were included. Among the former, mean CD4 cell count was 860/mm 3, 29(35%) patients had a previous AIDS diagnosis, 73(88%) were on HAART and HIV viremia was undetectable in 61(73%). No differences in cystatin C levels were observed between the 2 groups. In HIV-infected patients, cystatin C levels correlated with GFR (r = −0.27; P = 0.01), age at first HAART (r = −0.21; P = 0.05), and β-2-microglobulin (r = 0.569; P < 0.01). In multivariate analysis, lower GFR ( P = 0.014) and higher β-2-microglobulin levels ( P = 0.001) remained as independent risk factors for higher cystatin C values. Conclusions: Cystatin C values were associated with GFR and β-2-microglobulin. Cystatin C may be useful as a marker of renal function in HIV-infected pediatric patients, independently of ongoing inflammation or viremia.